The Role of Information in Medical Markets: An Analysis of Publicly Reported Outcomes in Cardiac Surgery - Cutler, David M; Huckman, Robert S; Landrum, Mary Beth (American Economic Review, 2004)
The Role of Information in Medical Markets: An Analysis of Publicly Reported Outcomes in Cardiac Surgery by David M. Cutler, Robert S. Huckman and Mary Beth Landrum. Published in volume 94, issue 2, pages 342-346 of American Economic Review, May 2004